2007
DOI: 10.1016/j.ejcts.2007.01.065
|View full text |Cite
|
Sign up to set email alerts
|

Clinical advantages of using mini-bypass systems in terms of blood product use, postoperative bleeding and air entrainment: an in vivo clinical perspective☆

Abstract: The adoption of mini-bypass significantly potentially reduces hemodilution, donor blood usage, postoperative bleeding and exposure to GME in routine CABG patients as compared to the use of conventional extracorporeal circulation circuits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 24 publications
2
28
0
9
Order By: Relevance
“…In several studies, the transfusion rate for different MECC systems could be reduced to 30-50% in comparison to standard CPB [14,15]. Several studies demonstrated that blood transfusion is an independent predictor of postoperative morbidity and mortality and, especially after CABG, every unit of RBC transfused is associated with an incrementally increased risk for adverse outcome [16,17].…”
Section: Commentmentioning
confidence: 98%
“…In several studies, the transfusion rate for different MECC systems could be reduced to 30-50% in comparison to standard CPB [14,15]. Several studies demonstrated that blood transfusion is an independent predictor of postoperative morbidity and mortality and, especially after CABG, every unit of RBC transfused is associated with an incrementally increased risk for adverse outcome [16,17].…”
Section: Commentmentioning
confidence: 98%
“…The use of antifibrinolytic, such as aprotinin, attenuates the systemic inflammatory response in patients undergoing EC [26]. The use of miniEC (reduction of the prime, the tubes and vacuum drainage) and the use of centrifugal pumps (Bio Pump) can reduce the excessive use of heparin [27,28]. Hypothermia (between 30° and 32° C) during the surgical procedure may also reduce bleeding during surgery and in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…This evolution of new knowledge minimized the deleterious effects of CPB and with the addition of accessories such as arterial filters and bubble detectors; it has reduced the morbimortality in cardiac surgery procedures with CPB [38,[43][44][45]. However, the incidence, still frequent of neurological complications remains a challenge because, despite all the advances, neurologic complications still occur and are causes of serious damage [4].…”
Section: Discussionmentioning
confidence: 99%